Observation of topological hydrogen-bonding domains in physical hydrogel for excellent self-healing and elasticity - Shaoning Zhang; Dayong Ren; Qiaoyu Zhao; Min Peng; Xia Wang; Zhitao Zhang; Wei Liu; Fuqiang Huang (Nature Communications)
Abstract Physical hydrogels, three-dimensional polymer networks with reversible cross-linking, have been widely used in many developments throughout the history of mankind. However, physical hydrogels face significant challenges in applications due to wound rupture and low elasticity. Some self-heal wounds with strong ionic bond throughout the network but struggle to immediately recover during cyclic operation. In light of this, a strategy that achieves both self-healing and elasticity has been developed through the construction of topological hydrogen-bonding domains. These domains are formed by entangled button-knot nanoscale colloids of polyacrylic-acid (PAA) with an ultra-high molecular weight up to 240,000, further guiding the polymerization of polyacrylamide to reinforce the hydrogel network. The key for such colloids is the self-assembly of PAA fibers, approximately 4 nm in diameter, and the interconnecting PAA colloids possess high strength, simultaneously acting as elastic scaffold and reversibly cross-linking near wounds. The hydrogel completely recovers mechanical properties within 5 h at room temperature and consistently maintains >85% toughness in cyclic loading. After swelling, the hydrogel has 96.1 wt% of water content and zero residual strain during cycling. Such physical hydrogel not only provides a model system for the microstructural engineering of hydrogels but also broadens the scope of potential applications.